Analysis of castor wheels rotation of mobile differential drive robot - A. A. Radkevich; Shixin Yang; U. A. Zaretski; A. A. Velchenko; S. A. Pauliukavets (Системный анализ и прикладная информатика)
Mathematical models for controlling centrally oriented and non-centrally oriented rotary wheels of a mobile robot are considered. Based on the analysis of the kinematics of the mobile robot, the dependences of the rotation angle of the rear and front free wheel on the angular velocities of the right and left differentially driven drive wheel were obtained. For a specific mobile robot with certain kinematic parameters, graphs of the dependences of the angle of rotation of the free wheels on the radius of rotation of each wheel and graphs of the dependences of the angle of rotation of the free wheels on the angular velocities of the driving wheels were constructed. The results obtained made it possible to establish a pattern between the angle of rotation of the castor wheels and the design characteristics of the robot. A certain range of angular velocities of the driving wheels in accordance with the limiting values of the caster wheel rotation angles makes it possible to take into account the obtained mathematical models to increase the stability of the movement of the mobile robot.